MENELAAH PAHAM KEBANGSAAN MUHAMMADIYAH - Infa Wilindaya (An-Nida', 2018)
The mission of Da'wah and the Tajajid Movement (Renewal) is an indisputable fact towards the birth of Muhammadiyah. How Kyai Dahlan thought ahead about building schools, changing the direction of the Gede Kauman Mosque, Al-Maun's theology by empowering the surrounding community is an example of the Muhammadiyah movement which is still engraved in every heart of the leadership of the congregation to this day.But the contact that finally collided with the nationality value that made Muhammadiyah out of the 'nest'. But of course this is inevitable, Muhammadiyah as one of the largest mass organizations in Indonesia in the practice of preaching will surely be dragged on the dynamics of national life